2009
DOI: 10.1590/s0101-31222009000100028
|View full text |Cite
|
Sign up to set email alerts
|

Alterações fisiológicas e bioquímicas durante a embebição de sementes de sucupira-preta (Bowdichia virgilioides Kunth.)

Abstract: RESUMO -Nessa pesquisa foi avaliado o comportamento das sementes de sucupira-preta durante a embebição, bem como as modificações em algumas proteínas durante esse processo. As sementes foram embebidas em rolo de papel umedecido, a 30°C e pesadas a cada 6 horas até a protrusão radicular de 50% das sementes, após o que as sementes foram submetidas a análises protéicas pela técnica da eletroforese. A curva de embebição dessa espécie segue um modelo trifásico. Na avaliação dos sistemas enzimáticos, foi observado u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 7 publications
1
13
0
5
Order By: Relevance
“…Albuquerque et al (2009) also found a reduction in band intensity of heat-resistant protein in seeds soaked for a longer time, near the root protrusion.…”
Section: Discussionmentioning
confidence: 76%
“…Albuquerque et al (2009) also found a reduction in band intensity of heat-resistant protein in seeds soaked for a longer time, near the root protrusion.…”
Section: Discussionmentioning
confidence: 76%
“…Through these studies, it may be inferred that the substrate and the temperature influence the seed germination, because when the germination process is started, metabolic reactions involving the activation of enzymes, hydrolysis, assimilation and mobilization of reserves, stretching and cell division are observed in the seeds (ALBUQUERQUE et al, 2009). Thus, in addition to the physiological activities that vary depending on the initial quality of the seed (MBOFUNG et al, 2013), the structure of the substrate, water retention capacity, aeration establishment and temperature also contribute to the increased percentage of germination (MARTINS et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…sulfuric acid 10', imb), at 30 O C (Table 2). Chemical and mechanic scarification caused fissures on the seeds testa of this study, which allows the absorption of water and oxygen (Martin et al, 2008), enzymatic activation and energetic reserves hydrolysis, resulting in cell division and elongation and a faster and more constant germination (Albuquerque et al, 2009).…”
Section: Resultsmentioning
confidence: 81%